The Boma: International Women's Day 2022 - International Livestock Research Institute (International Livestock Research Institute, 2022)
Livestock provide vital nutrition and income for numerous households in developing countries. And it's often women who do the bulk of the work caring for the animals. But this doesn't mean they reap the benefits. In many communities, women are excluded from making management decisions about livestock, like when to sell them, or how to treat them. They also don't get to control the income that the livestock generate, or the valuable livestock products made. And this is particularly the case for the larger, more valuable animals, like cattle. How can livestock farming help build gender equality in such communities, instead of repeating traditional and unequal gender norms? ILRI’s research is part of many worldwide efforts to empower women and girls. The second season of The Boma kicks off with an episode for International Women's Day 2022, taking a close look at ILRI's Women in Business project, which empowers women to benefit from chicken farming in Ethiopia and Tanzania. Presenters and Princeton-in-Africa Fellows Brenda Coromina and Elliot Carleton talk to Alessandra Galiè, Gender Team Leader at ILRI, Upendo Ramadhani Simba, a university graduate of animal sciences who began as a chicken vendor through the project, and Adolf Jeremiah, a research field coordinator at ILRI with a background on gender and youth programming.